Efektivitas Melodic Intonation Therapy pada Afasia Tidak Lancar: Studi Meta-Analisis - Sadiah, Hikmatun; Taruna, Rexsy (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2022)
Introduction: Melodic intonation therapy (MIT) is one of the intervention strategies to improve verbal skills in non-fluent aphasia patients.Aim: To synthesize the effectiveness of MIT on naming skills and speech repetition in individuals with post-stroke non-fluent aphasia.Methods: This research has a systematic review and meta-analysis design. Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) flow diagrams were used in this study, with three associated databases (Pubmed, Gale OneFile, and CENTRAL). Four experimental articles with a randomized controlled trial (RCT) designs were included in this meta-analysis.Results: Based on the results of data synthesis, it is known that MIT significantly affects speech repetition ability (Standardized Mean Difference (SMD)=0.75; p<0.0002; 95% CI 0.36–1.15) when compared to naming ability (SMD=0.34; 95% CI -0.10–0.78).Discussion: Giving MIT for eight weeks (5 times per week, 30 minutes per day) has the most significant effect size on speech repetition ability.